1982
DOI: 10.1177/0049124182011001005
|View full text |Cite
|
Sign up to set email alerts
|

Validity of Forced Responses in a Randomized Response Model

Abstract: An empirical test was conducted to determine the degree to which respondents would follow the directions of the randomizing device in the directed response model of the randomized response technique (RRT). The results showed that a sizable percentage of the respondents would not give the directed response to a question if that response was a socially undesirable one and the question was sufficiently sensitive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
1

Year Published

1985
1985
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 14 publications
1
40
1
Order By: Relevance
“…For example, in an FC study reported by Edgell et al (1982) respondents were asked to say 'Yes' when the outcome of a randomizing device is 0 and 1, 'No' when the outcome is 8 and 9, and to answer honestly for outcomes between 2 and 7. By fixing outcomes of the randomizing design a priori, the investigators found that about 25% of the respondents did not follow the instructions when answering a question on homosexual experiences: They answered 'No' although they should have responded 'Yes' according to the randomizing device.…”
Section: Non-pseudo-incriminators and Self-protective Respondentsmentioning
confidence: 99%
“…For example, in an FC study reported by Edgell et al (1982) respondents were asked to say 'Yes' when the outcome of a randomizing device is 0 and 1, 'No' when the outcome is 8 and 9, and to answer honestly for outcomes between 2 and 7. By fixing outcomes of the randomizing design a priori, the investigators found that about 25% of the respondents did not follow the instructions when answering a question on homosexual experiences: They answered 'No' although they should have responded 'Yes' according to the randomizing device.…”
Section: Non-pseudo-incriminators and Self-protective Respondentsmentioning
confidence: 99%
“…This design was created to address the problem that under the other randomized response designs some respondents may still feel uncomfortable providing a particular response (e.g., answering "yes") even when interviewers do not know whether they are answering the sensitive question. For example, Edgell, Himmelfarb, and Duchan (1982) used the forced response design to study college students' experiences with homosexuality. By fixing the outcome of the randomization device unbeknownst to the respondents, the researchers found that 25% of the respondents who were forced to reply "yes" by design did not do so.…”
Section: Disguised Response Designmentioning
confidence: 99%
“…Under the standard forced response design, we assume that both the probability of answering the sensitive question p and that of a forced "yes" ("no") p 1 (p 0 ) are known. However, respondents may not reply "yes" even when forced to do so (Edgell, Himmelfarb, and Duchan 1982). The modified forced response design addresses such noncompliance behavior.…”
Section: Forced Response Design Withmentioning
confidence: 99%
See 1 more Smart Citation
“…The RD is specified in such a way that the sensitive question is selected with probability ϕ 1 and the unrelated question with probability 1 − ϕ 1 . This RR method is extended to a forced response method (Edgell, Himmelfarb, & Duchan, 1982), where the unrelated question is not specified but an additional RD is used to generate a forced answer. Each observed individual answer is protected, since it cannot be retrieved whether it is a true answer to the sensitive question or a forced answer generated by the RD.…”
Section: Multivariate Randomized Response Techniquesmentioning
confidence: 99%